2004
DOI: 10.1080/1361767042000199004
|View full text |Cite
|
Sign up to set email alerts
|

Psychological type and sex differences among church leaders in the United Kingdom

Abstract: A sample of 135 female and 164 male church leaders of mixed denominations completed the Francis Psychological Type Scales. The female church leaders demonstrated clear preferences for extraversion over introversion, for sensing over intuition, for feeling over thinking, and for judging over perceiving. The male church leaders demonstrated clear preferences for introversion over extraversion, for sensing over intuition, for thinking over feeling, and for judging over perceiving. The predominant type among the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

8
2

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…First, this preference is close to the preference expressed by Church of England clergymen in the study reported by Francis, Craig, Whinney, Tilley, and Slater [15], where 57% preferred introversion. Second, the preference for introversion varies among the other five groups of women involved in ministry for whom profiles are available: 54% of 213 female Bible College students reported by Francis, Penson, and Jones [16], 50% of 192 female evangelical church leaders reported by Francis, Craig, Horsfall, and Ross [21], 46% of 122 female Pentecostal Bible College students reported by Kay and Francis [22], 41% of 135 female church leaders reported by Craig, Francis, and Robbins [23], and 41% of 134 female Christian youth workers reported by Francis, Nash, Nash, and Craig [14]. Further research is needed to confirm whether such a strong preference is really characteristic of Church of England clergywomen.…”
Section: Profiling Clergymen and Clergywomen In The Ukmentioning
confidence: 99%
“…First, this preference is close to the preference expressed by Church of England clergymen in the study reported by Francis, Craig, Whinney, Tilley, and Slater [15], where 57% preferred introversion. Second, the preference for introversion varies among the other five groups of women involved in ministry for whom profiles are available: 54% of 213 female Bible College students reported by Francis, Penson, and Jones [16], 50% of 192 female evangelical church leaders reported by Francis, Craig, Horsfall, and Ross [21], 46% of 122 female Pentecostal Bible College students reported by Kay and Francis [22], 41% of 135 female church leaders reported by Craig, Francis, and Robbins [23], and 41% of 134 female Christian youth workers reported by Francis, Nash, Nash, and Craig [14]. Further research is needed to confirm whether such a strong preference is really characteristic of Church of England clergywomen.…”
Section: Profiling Clergymen and Clergywomen In The Ukmentioning
confidence: 99%
“…This research tradition has more recently been extended to the United Kingdom with studies reported among Anglican clergy (Francis, priests (Craig, Duncan, & Francis, 2006), Bible College students (Francis, Penson, & Jones, 2001;Kay, Francis & Craig, 2008), Evangelical church leaders (Francis & Robbins, 2002), interdenominational church leaders (Craig, Francis, & Robbins, 2004), missionary personnel (Craig, Horsfall, & Francis, 2005), youth ministers (Francis, Nash, Nash, & Craig, 2007), and Evangelical seminarians (Francis, Craig, & Butler, 2007). Two main conclusions can be drawn from this developing body of research.…”
Section: In Theirmentioning
confidence: 99%
“…These studies include, for example, Anglican Church in Wales clergymen (Francis, Payne, & Jones, 2001;Francis & Payne, 2002), male and female Bible college students (Francis, Penson, & Jones, 2001), evangelical church leaders (Francis & Robbins, 2002;Craig, Francis, & Robbins, 2004), male missionary personnel , evangelical lay church leaders (Francis, Craig, Horsfall, & Ross, 2005), Roman Catholic priests (Craig, Duncan, & Francis, 2006), youth ministers (Francis, Nash, Nash, & Craig, 2007), evangelical Anglican seminarians (Francis, Craig & Butler, 2007), Assemblies of God theological college students (Kay, Francis, & Craig, 2008;, Newfrontiers lead elders (Francis, Gubb, & Robbins, 2009), Newfrontiers leaders (Ryland, Francis, & Robbins, in press), and Anglican health-care chaplains (Francis, Hancocks, Swift, & Robbins, 2009). …”
Section: Psychological Type Theorymentioning
confidence: 99%